2023
DOI: 10.1371/journal.pone.0290845
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of β-lactamase function by de novo designed peptide

Arunima Mishra,
Irena Cosic,
Ivan Loncarevic
et al.

Abstract: Antimicrobial resistance is a great public health concern that is now described as a “silent pandemic”. The global burden of antimicrobial resistance requires new antibacterial treatments, especially for the most challenging multidrug-resistant bacteria. There are various mechanisms by which bacteria develop antimicrobial resistance including expression of β-lactamase enzymes, overexpression of efflux pumps, reduced cell permeability through downregulation of porins required for β-lactam entry, or modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Even more the RRM model describes this complex relationship through single number representing resonant frequency for all constituents in the process of myelin existence. Once when such characteristic frequency has been identified, we can use it to design de novo peptides, as we did successfully in number of other examples [15][16][17][18][19][20][21][22][23][24], that would be able to repair damaged myelin, which possibly could be used for treatment of MS and AD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even more the RRM model describes this complex relationship through single number representing resonant frequency for all constituents in the process of myelin existence. Once when such characteristic frequency has been identified, we can use it to design de novo peptides, as we did successfully in number of other examples [15][16][17][18][19][20][21][22][23][24], that would be able to repair damaged myelin, which possibly could be used for treatment of MS and AD.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we have identified that all participants in the myelin formation and stability, both proteins and cholesterol as small molecule, do have only one common RRM frequency at f=0.1953±0.0060, indicating that this frequency is critical for myelin formation and stability. With such identified RRM characteristic frequency, the next step would be to design de novo bioactive peptides using already established and successfully tested RRM procedure [15][16][17][18][19][20][21][22][23][24]. Such designed peptides might be able to facilitate repair of damaged myelin and could lead to new possible treatment of MS and AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation